2020
DOI: 10.18325/jkmr.2020.30.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of East-West Integrative Rehabilitation on Activities of Daily Living and Cognitive Functional Recovery in Stroke Patients: A Retrospective Study

Abstract: Objectives This study was conducted to verify the effectiveness of east-west integrative rehabilitation therapy on activity of daily living and cognitive functional recovery in stroke patients by comparing with integrative rehabilitation therapy group and conventional rehabilitation therapy group in a single institution. Methods The medical records of 106 stroke patients hospitalized in Department of Rehabilitation Medicine, Dongguk University Bundang Oriental Hospital from January 1, 2017 to February 28, 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…This study indicated that the main reason for these findings and the differences from the results of the previous study was the recent increase in the use of KM and KM&WM as CT among elderly individuals [ 20 , 21 , 22 ]. Therefore, we investigated the social, policies, economic and scientific causes based on the above research results.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…This study indicated that the main reason for these findings and the differences from the results of the previous study was the recent increase in the use of KM and KM&WM as CT among elderly individuals [ 20 , 21 , 22 ]. Therefore, we investigated the social, policies, economic and scientific causes based on the above research results.…”
Section: Discussioncontrasting
confidence: 69%
“…However, the limitation of this finding was that it only included consultations for acupuncture medicine. Although the validation of the medical effect of CT in several medical fields is incomplete, the efficacy of Non-HM for disease is gradually being scientifically proven [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, more than 30% of stroke patients have difficulties in performing independent activities of daily living [4]. Therefore, a rehabilitation treatment approach is important for stroke patients to overcome obstacles and independently perform daily life [5], and evaluating and performing the patient's daily activities after stroke is very important in achieving the patient's rehabilitation goal. It is important and is the most basic for the patient's independent life [6].Stroke patients require long-term rehabilitation, and this burden causes them to experience financial stress [7].…”
mentioning
confidence: 99%